Metagenomic analysis of gut microbiota diversity in poultry before and after antibiotic administration - O. V. Prasolova; N. I. Malik; I. A. Timofeeva; N. A. Kirsanova; E. V. Krylova; E. V. Malik; I. A. Rusanov; N. A. Chupakhina (Ветеринария сегодня)
The diversity of gut microbiota is an important ecological resource that plays a key role in maintenance of the host homeostasis. It is extremely important to preserve the existing gut microbiota diversity, which ensures its resistance to the negative effects of abiotic factors, while the study of the antibiotic role in the disturbance of microbiota diversity is a fundamental basis used not only to identify aspects responsible for microbiota-associated poultry diseases, but also to learn techniques of microbiota management. This study gives a characteristic of poultry gut microbiota diversity before and after antibiotic administration based on 16S rRNA gene sequencing analysis. Firmicutes and Bacteroidota species were predominantly detected in the chick microbiota during antibiotic administration and after its withdrawal. A significant increase in Patescibacteria abundance was observed on day 11 post enrofloxacin cessation. Actinobacteriota started appearing on day 11 after antibiotic discontinuation. An increase in Cyanobacteria abundance was detected on day 4 after the drug withdrawal. Taxonomic shifts in the chick microbial community structure at the class level both during the antibiotic treatment and after its withdrawal were observed. The abundance of Clostridia and Bacteroidia classes tended to decrease, while Bacilli class increased in its abundance, especially on day 8 after the drug withdrawal. It was found that a ten-day course of enrofloxacin treatment at the recommended doses leads to an increase in the abundance of Bacillaceae, Gastranaerophilales, Lactobacillaceae, Bacteroidaceae, Bifidobacteriaceae families, while the abundance of Rikenellaceae, Erysipelatoclostridiaceae, Clostridiaceae, Ruminococcaceae decreased and did not affect the abundance of Lachnospiraceae family. The revealed increase in the proportion of Lactobacillaceae during antibiotic treatment suggests the ability of a healthy organism to restore the microbiota balance. The results of metagenomic data bioinformatics (without truncation) showed the presence of 158 microorganism species in the chick microbiota, 38% of which were classified as nonculturable.